KCNMB2-AS1 Promotes Bladder Cancer Progression Through Sponging miR-374a-3p to Upregulate S100A10 - Zhu, Jianhua; Huang, Yan; Zhang, Yong; Huang, Rongfu; Huang, Chunmei (Frontiers in Genetics, 2021)
Long noncoding RNAs (lncRNAs) have been reported to play crucial role in the pathogenesis of numerous cancers. However, the function of lncRNA KCNMB2-AS1 in bladder cancer (BC) remains unclear. In the present study, we aimed to explore the role and underlying mechanisms of KCNMB2-AS1 in bladder cancer progression. We found lncRNA KCNMB2-AS1 was significantly upregulated both in BC tissues and cell lines, the expression level was highly correlated with pathological TNM stage. Functionally, knockdown of lncRNA KCNMB2-AS1 dramatically inhibited the proliferation, migration and invasion and of BC cells in vitro, and suppressed tumor growth in vivo. Mechanistically, lncRNA KCNMB2-AS1 could function as a competitive endogenous RNA (ceRNA) through direct sponging miR‐374a-3p, which regulating the expression of S100A10. In conclusion, our results demonstrated that lncRNA KCNMB2-AS1 can promote the progression of bladder cancer through regulation of miR-374a-3p/S100A10.